UNDERGRADUATES’ AWARENESS OF WAQF (ENDOWMENT): AN EMPIRICAL ANALYSIS BASED ON STATE UNIVERSITIES IN SRI LANKA - Firnas, Zain Fazley Zainul; Saujan, Iqbal; Nafees, Seni Mohamed Mohamed (International Journal of Sukuk and Waqf Research, 2024)
The study aims to assess awareness of Islamic waqf among undergraduates pursuing primary degrees in Sri Lanka’s state universities. The study adopted a descriptive approach, focusing on quantitative data analysis. The data were collected through questionnaire distribution among 300 participants from randomly selected state universities, which received 270 (90% response rate) usable questionnaires. The data analysis was conducted using SPSS software (Version 26), which used descriptive and inferential statistics. The results were organised into tables and graphs to help provide a better understanding. The findings reveal that although undergraduates acquire a superficial understanding of the concept of Islamic Waqf, they lack awareness regarding its procedures, conditions, purposes, appointment of trustees (Mutawalli), significant relation between waqf charitable enforcement and sustainable development in the economy, and the issue of waqf to non-Muslims. This knowledge gap can be attributed to inadequate knowledge provided by governmental and voluntary organisations for individuals to participate in and support the Islamic Waqf Institutions, which is essential for actively understanding the procedures and conditions. By educating individuals about Waqf procedures and conditions, individuals can obtain knowledge and contribute to ensuring that the resources are utilised effectively for sustainable economic growth. Implementing the Waqf Charitable endowment in areas such as Education Waqf, Medical Waqf, and Provident Fund Waqf will remain challenging without addressing this issue. Hence, policymakers and relevant authorities should prioritise improving awareness and understanding of Islamic waqf between the literary community and the public.JEL Classification Codes: G32, F65, L66, L25, M41.